Deiksis dalam Film Bumi dan Manusia Karya Hanung Bramantyo - Azaa Izzatul Laila; Ahmad Firdaus; Zahra Nurainnisa Suhendar; Winda Dwi Hudhana; Asep Purwo Yudi Utomo (Pusat Riset dan Inovasi Nasional, 2022)
Deixis is a pragmatic study that examines the relationship between the structure of language and the environment in which the language is used. The phenomenon of deixis or use is most often seen in everyday conversation in the form of verbal language. Deixis is also found in the conversation of characters or figures in literary works such as films. The study entitled